A STABILITY INDICATING MICELLAR LIQUID CHROMATOGRAPHIC METHOD FOR THE DETERMINATION OF DEFERASIROX IN SOLUBILIZED SYSTEM - Malvia, Hitesh; Kumar, Ashok; Sharma, Pratibha; Mishra, Ritesh (Journal of Drug Delivery and Therapeutics, 2017)
A simple, isocratic and stability indicating micellar liquid chromatographic (MLC) method containing a surfactant solution above its critical micellar concentration (CMC) was developed and validated for determination of Deferasirox (BTBA) content in active pharmaceutical ingredient and its pharmaceutical formulations. The analysis was performed in on isocratic mode at 400C temperature through Thermo Hypersil ODS 100mm×4.6mm, 3 µm particle size columns. The UV detection wavelength was set at 250 nm in the mobile phase containing 0.1 M Cetyl trimethyl ammonium bromide (CTAB) buffer (pH – 2.5) and 10% 1-butanol. The method was successfully validated following as per the requirements of ICH guidelines. The proposed method was successfully applied as stability indicating method for determination of BTBA under different stressed conditions. The method allows accurate and reliable determination of BTBA for drug stability assay in pharmaceutical investigations.